A Critical Theory of Creativity - Howells, R. author. aut Link
VII, 204 p.
Keywords: A Critical Theory of Creativity argues that a Utopian drive is aesthetically encoded within the language of form. But coupled with this opportunity comes a very human obligation which cannot be delegated to God, to nature or to market forces. As Ernst Bloch declared: 'Life has been put into our hands.'.